Open Radical Cystectomy versus Robot-Assisted Radical Cystectomy with Intracorporeal Urinary Diversion: Early Outcomes of a Single-Center Randomized Controlled Trial. Issue 5 (2nd May 2022) - Mastroianni, Riccardo; Ferriero, Mariaconsiglia; Tuderti, Gabriele; Anceschi, Umberto; Bove, Alfredo Maria; Brassetti, Aldo; Misuraca, Leonardo; Zampa, Ashanti; Torregiani, Giulia; Ghiani, Edoardo; Giannarelli, Diana; Guaglianone, Salvatore; et al.
Abstract : Purpose: Radical cystectomy (RC) with urinary diversion (UD) is still considered a complex surgery associated with significant morbidity. Open RC (ORC) remains the reference option of treatment, even if adoption of robot-assisted RC (RARC) is rapidly increasing. To date, all the available randomized controlled trials were characterized by an extracorporeal approach in performing UD, undermining potential benefits of a totally minimally invasive procedure. In this study, we aimed to report perioperative and 6-month outcomes from the first RCT comparing ORC and RARC with totally intracorporeal UD. Materials and Methods: Patients were eligible for randomization if they had a diagnostic transurethral resection of bladder tumor with cT2-4, cN0, cM0 or recurrent high-grade nonmuscle-invasive bladder cancer and no anesthesiological contraindications to robotic surgery. Patients were enrolled with a covariate adaptive randomization process based on the following variables: body mass index, American Society of Anesthesiologists® score, baseline hemoglobin, planned UD, neoadjuvant chemotherapy and cT stage. The primary end point was to demonstrate the superiority of RARC with intracorporeal UD in terms of a 50% transfusion rate reduction. Results: Overall, 116 consecutive patients (58 RARC, 58 ORC) were enrolled. Among primary endpoint, overall perioperative transfusion rates were significantly lower in the RARC cohort (RARC: 22% vs ORC: 41%; p=0.046). Conclusions: This prospective randomized trial observed 22% and 41% overall perioperative transfusion rates in patients treated by RARC and ORC, respectively, confirming a significant benefit in favor of RARC with intracorporeal UD. However, perioperative complications, hospital stay and 6-month health-related quality of life were largely comparable between groups. Oncologic and functional outcomes will be assessed at longer followup to observe potential differences between arms.